Emergency Vehicle oriented Traffic Priority Control Strategy at Intersection in Congested Urban Area - Yao Jiao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Efficient and safe traffic control strategy for emergency vehicle can reduce its travel time and avoid secondary accident. Based on the analysis of its requirement and object, we proposed a novel control strategy at intersection according to the status of emergency vehicle, which can be divided into three parts: “approaching”, “passing “and “recovering”, Furthermore potential safety risk caused by emergency vehicle was also taken into account when making control strategy.From the case study we conclude that with control strategy in this paper delay of emergency vehicle can be sharply decreased by 68.63% with only 19.86% loss of average delay of background traffic.  DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4928